2014
DOI: 10.1016/j.jvs.2013.08.099
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Quality of Life Questionnaire-6 facilitates health-related quality of life assessment in peripheral arterial disease

Abstract: VascuQoL-6 is a valid and responsive instrument for the assessment of health-related quality of life in PAD. The main advantage is the compact format that offers a possibility for routine use in busy clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 19 publications
1
78
0
Order By: Relevance
“…These results suggest that Vascu-QOL can be a potential quantitative method to suspect the existence of CLI in dialysis PAD patients. One more advantage of VascuQOL over SPP is easy for every health professional to administer, score, and analyze without using any specific measuring machine [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that Vascu-QOL can be a potential quantitative method to suspect the existence of CLI in dialysis PAD patients. One more advantage of VascuQOL over SPP is easy for every health professional to administer, score, and analyze without using any specific measuring machine [26].…”
Section: Discussionmentioning
confidence: 99%
“…Vascu-QOL consists of simple questionnaire, but the number of questions might be large for older patients. Actually, a trial to reduce the number of questions has been already performed [26]. Several domains such as "Pain", "Symptom," and "Emotional" can be selected and assessed in the future studies to achieve better compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, all items in the VascuQol have seven response options, which could very well be too many. Indeed, in a recent study, Nordanstig et al 7 found through cognitive interviews that many patients mentioned the abundance of response options. This may also cause patients to fill items at random, which influences outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As specified in Appendix 2 (Supporting Information Appendix S2), when assessing GPS outdoor walking capacity in PAD patients, some authors have used the total walking distance measured during a 40-min outdoor walk (Nordanstig et al, 2014a(Nordanstig et al, , 2014b, whereas others have used the highest measured distance between two stops (Le Faucheur et al, 2008Faucheur et al, , 2010Tew et al, 2013). The difference in the outcome measures computed seems to be a direct consequence of the GPS analysis methodology used.…”
Section: Clinical Interpretationmentioning
confidence: 99%